2009
DOI: 10.1148/radiol.2513081732
|View full text |Cite
|
Sign up to set email alerts
|

Iodixanol, Constriction of Medullary Descending Vasa Recta, and Risk for Contrast Medium–induced Nephropathy

Abstract: Purpose:To determine whether a type of contrast medium (CM), iodixanol, modifies outer medullary descending vasa recta (DVR) vasoreactivity and nitric oxide (NO) production in isolated microperfused DVR. Materials and Methods:Animal handling conformed to the Animal Care Committee Guidelines of all participating institutions. Single specimens of DVR were isolated from rats and perfused with a buffered solution containing iodixanol. A concentration of 23 mg of iodine per milliliter was chosen to mimic that expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 40 publications
5
82
1
3
Order By: Relevance
“…ROS may also deregulate the adaptive cellular mechanisms during hypoxia. A reduced synthesis of NO has been shown in isolated vasa recta perfused with CM, and the adverse effects of CM have been prevented by ROS scavengers [44]. Thus, there is an important imbalance in the regulation of vascular tone towards vasoconstriction.…”
Section: Pathophysiology Of Contrast-induced Nephropathymentioning
confidence: 99%
“…ROS may also deregulate the adaptive cellular mechanisms during hypoxia. A reduced synthesis of NO has been shown in isolated vasa recta perfused with CM, and the adverse effects of CM have been prevented by ROS scavengers [44]. Thus, there is an important imbalance in the regulation of vascular tone towards vasoconstriction.…”
Section: Pathophysiology Of Contrast-induced Nephropathymentioning
confidence: 99%
“…Pre-glomerular vasoconstriction is one reason behind CM-induced reduction in GFR [38], such as observed here upon iodixanol injection (Figure 3) [29]. Vasoconstriction of post-glomerular vessels including the descending vasa recta (DVR) will result in medullary hypoxia, and, thus, promote the vicious circle [29,39].…”
Section: Issn: 2380-0585mentioning
confidence: 73%
“…Medullary hypoperfusion relies on increased resistance to blood flow, due to, descending vasa recta vasoconstriction, among other factors. In both the cortex and the medulla, CM can shift the balance between vasodilatory and vasoconstrictive factors towards vasoconstriction [16,17]. Because medullary perfusion comprises <10% of total renal blood flow, the vasoconstrictive response of total renal blood flow to CM observed in several studies reflects cortical rather than medullary effects.…”
Section: Pathophysiology Of Cinmentioning
confidence: 99%
“…Larson et al [22] have successfully induced acute renal failure in animal models by administration of a contrast media bolus, and they found that sodium depletion accentuated both the magnitude and duration of the vasoconstrictive phase of the renal blood flow response to the injection of contrast medium and that blockade of the intrarenal renin-angiotensin system shortened the duration of this response. In addition, there is evidence that iodixanol, a nonionic, dimeric contrast media, causes increased oxidative stress and decreased nitric oxide production in outer medullary descending vasa recta, with consequent constriction of the descending vasa recta and increased reactivity to angiotensin II [16]. Activation of RAAS could also cause vasoconstriction of the efferent glomerular arteriole while simultaneously increasing the ex novo synthesis of vasodilator prostaglandins resulting in nearly stable or slightly increased intrarenal resistance.…”
Section: The Role Of Raas In Cinmentioning
confidence: 99%